Vascularized Bone Grafting for Scaphoid Nonunion with Humpback Deformity: The Surgical Technique - Kawasaki, Keikichi (J Wrist Surg, 2020)
Background  Scaphoid nonunion with humpback deformity and avascular necrosis (AVN) is a challenging problem. Correction of dorsal intercalated segment instability (DISI) requires grafting of a large and hard vascularized bone segment onto the volar side of the scaphoid. Purposes  We have been treating the patients with one-incision vascularized bone grafting technique for scaphoid nonunion to improve blood supply and correct humpback deformity. We evaluated these cases retrospectively to the surgical efficacy of our procedure. Methods  We harvested vascularized bone from the dorsal side of the radius using the method by Zaidemberg et al and inserted the cortical aspect into the scaphoid volar side using a direct lateral approach. Totally, 11 patients (nine males andtwo females) with a mean age of 40 years were recruited for this study. The mean time from fracture to treatment was 6 years and 3 months. The mean preoperative radiolunate angle was 25 degrees. All the patients showed AVN of the proximal scaphoid on T1-weighted images. An averaged follow-up period was 2 years and 3 months. Results  Postoperative computed tomography revealed bony union in 10 patients (91% of union rate) with a mean modified Mayo'swrist score of 88 points (range, 75–100 points) and a mean disabilities of arm, shoulder, and hand (DASH) score of 4 points (range, 0–20 points). The mean radiolunate angle was corrected from 25 to 5 degrees. No adverse events were observed, except temporary mild paresthesia of the radial nerve territory in two patients. Conclusion  This technique effectively corrected DISI in patients with scaphoid nonunion accompanied by humpback deformity and AVN.